Detection of foreign bodies in the canine stomach using capsule endoscopy: a randomized trial - Kim, Ui-Yeon; Kim, Young Joo; Lee, Joon Woo; Kim, Munso; Jang, Hyomi; Jung, Dong-In (Frontiers in Veterinary Science, 2024)
This study aimed to assess the effectiveness of capsule endoscopy in detecting gastric foreign bodies in normal dogs, considering variations in the number of foreign bodies and the gastric environment. Methods: Five healthy male beagles were administered virtual, non-harmful foreign objects that maintained their shape in the stomach. Capsule endoscopy was performed and the images were evaluated by veterinarians and non-veterinarians. Results: The overall sensitivity and specificity of capsule endoscopy were 99.1% and 90.4%, respectively. Sensitivity and specificity were comparable between veterinarians and non-veterinarians. Sensitivity and specificity in the veterinarian group were 98.7% and 91.2%, respectively, whereas those in the non-veterinarian group were 100% and 88.5%, respectively. Discussion: Capsule endoscopy is a valuable alternative diagnostic tool for identifying foreign bodies in the stomach, particularly in challenging cases in which conventional imaging or invasive approaches have limitations.